Common Fixed Point Theorems for a Rational Inequality in Complex Valued Metric Spaces. (24th October 2013) - Kumar, Pankaj; Kumar, Manoj; Kumar, Sanjay
Abstract : We prove a common fixed point theorem for a pair of mappings. Also, we prove a common fixed point theorem for pairs of self-mappings along with weakly commuting property.